2017
DOI: 10.1167/iovs.17-22788
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Retinal Vein Occlusion

Abstract: Experimental animal models of RVO are available to study the pathogenesis of this disease and to evaluate diagnostic/prognostic biomarkers and to develop new therapeutics. Data available suggest laser-induced RVO in pigs and rodents to be overall the best models of BRVO and the laser-induced RVO rodents the best model for CRVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 193 publications
(692 reference statements)
0
40
0
Order By: Relevance
“…The study also reported that most animal models of RVO demonstrated spontaneous reperfusion and/or vascular remodeling, which seemed to occur more rapidly and effectively than in humans with RVO. 14 The period needed for developing collateral vessels to mature was much shorter in our model than that in human eyes, 27 possibly because the animals used for RVO models were young and healthy, whereas patients with RVO are often older and many have underlying systemic disorders, such as hypertension, dyslipidemia, dysfunctional thrombotic responses, or impaired glucose tolerance/diabetes, among others. 14 Because RVO in our animal model was artificially and acutely induced by laser photocoagulation, the process of the condition forming the RVO would be different than clinical cases.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The study also reported that most animal models of RVO demonstrated spontaneous reperfusion and/or vascular remodeling, which seemed to occur more rapidly and effectively than in humans with RVO. 14 The period needed for developing collateral vessels to mature was much shorter in our model than that in human eyes, 27 possibly because the animals used for RVO models were young and healthy, whereas patients with RVO are often older and many have underlying systemic disorders, such as hypertension, dyslipidemia, dysfunctional thrombotic responses, or impaired glucose tolerance/diabetes, among others. 14 Because RVO in our animal model was artificially and acutely induced by laser photocoagulation, the process of the condition forming the RVO would be different than clinical cases.…”
Section: Discussionmentioning
confidence: 95%
“…The study that comprehensively reviewed animal RVO models has reported that all RVO models revealed early features classically observed in human, including cessation of blood flow and venous dilation, engorgement, and tortuosity distal to the occlusion site. 14 Moreover, the models generally demonstrated retinal hemorrhages and edema, which may make them suitable models to study the acute phase of RVO. 14 In our RVO model, those early characteristic features were found, indicating that our model can be considered suitable to study the acute phase of RVO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…these models have been used to improve the understanding of this condition and have shown their value on this regard (149) .…”
Section: A Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…Nevertheless, several animal models of vascular occlusion using laser photocoagulation, photodynamic coagulation, intravitreal injection of dermal fibroblasts, and diathermic cauterization have been proposed. 26 Among them, the photodynamic coagulation method 27 shows early features of the clinical disease, including retinal capillary dropout, hemorrhage, and edema. Herein, we developed an easy and reproducible model of CRVO in mice, which is particularly useful when analyzing genetically modified mice.…”
mentioning
confidence: 99%